Listening Comprehension Anxiety: Causes and Suggestive Strategies for Solutions - Mohammad Qasim Farooqi (Jurnal Multidisiplin Madani, 2023)
The present study aimed to explore the factors causing listening comprehension anxiety (LCA) for the Afghan English major students  and the strategies they used as solutions to reduce their listening anxiety. The participants (n=8) were chosen through a purposive sampling technique from the English Department of Education Faculty at Badghis Institute of Higher Education  The study employed a qualitative research design where semi-structured interviews were conducted to collect data from the participants. After collecting the data, they were transcribed, analyzed, and eight significant themes emerged. The themes included the participants' LCA factors and strategies they used to reduce their anxiety in a listening activity. Teachers and learners could use the findings from this study worldwide to enhance students' listening comprehension and reduce their LCA